FORMS AND STAGES OF IMPLEMENTATION OF CORPORATE GOVERNANCE PRINCIPLES IN THE UNIVERSITY GOVERNANCE PROCESS - Abdukarimovich, Abdurasulov Abdullajon (The journal of contemporary issues in business and government, 2021)
The article emphasizes that at the new stage of Uzbekistan's development, one of the urgent tasks is the introduction of corporate governance principles in the management of universities and the creation of a special model of higher education, taking into account its characteristics.